Learning to Plan for the Future Through the Tree of Hope Activity: Literacy Movement at Tanzil KG Lindungan Selangor, Malaysia - Lasmiatun, Lasmiatun; Layla, Regita (Jurnal PKM Manajemen Bisnis, 2025)
The Tree of Hope activity is an innovative program implemented in Malaysia to help children of Indonesian migrant workers plan for their future. This case study was conducted at At Tanzil Learning Center, Lindungan Village involving 45 students in grades 1-4 aged 5-12 years old. Using a mixed method of lectures and practical exercises, the activity aimed to help the children express their aspirations visually and verbally. The activity process included showing educational videos about various professions, making a wish tree, and sharing stories about aspirations. The results showed that the most popular professions were TNI (20%), Police (17.8%), Doctor (15.6%), Teacher (13.3%), and Firefighter and Pilot (11.1% each). This activity not only succeeded in increasing the children's motivation and confidence, but also created a fun and interactive learning environment. The program has proven to be effective in providing psychological and social support for immigrant children, as well as building a community that supports each other in achieving common goals. Through this creative approach, Tree of Hope contributes positively to the development and future of Indonesian migrant worker children in Malaysia.